Three-year longitudinal fitness tracking in top-level competitive youth ice hockey players - Cordingley, M. D.; Sirent, L.; MacDonald, P. B.; Leiter, J. R. (The Journal of Strength and Conditioning Research, 2019)
The purpose of this retrospective review was to report the physical and physiological development of top-level competitive male youth hockey players for 3 consecutive years (13, 14, and 15 years of age). Before each hockey season, the athletes (n = 103) underwent a fitness testing combine to assess aerobic, anaerobic, and musculoskeletal fitness. The tests performed included the height, body mass, body fat percentage determined by skinfolds, push-ups, chin-ups, plank, broad jump, grip strength 20-m shuttle run, Wingate bike test, and 5-10-5 shuttle test. Height and body mass increased with each consecutive year (p < 0.05) with no change in body fat percentage. Chin-ups, broad jump, and grip strength all improved with age (p < 0.001). However, push-ups only improved from 13 to 14 years of age (p < 0.001), whereas maximal plank duration decreased from 14 to 15 years of age (p < 0.05). The total distance covered during the 20-m shuttle run decreased from 14 to 15 years of age (p < 0.05). Absolute peak and average power increased with each age increase (p < 0.001), but relative peak and average power only increased from 13 to 14 years of age (p < 0.05). There was no change in the fatigue index with age. The 5-10-5 shuttle test improved with each age increase (p < 0.05). Over a 3-year period (13-15 years of age), there are many physical and physiological changes that occur in top-level competitive male hockey players. Having a better understanding of how these athletes develop could aid in the implementation of specific on- and off-ice training programs.